Synthesis And Electrochemical Behavior Of Lifepo4/C With Air-Electrode For Aqueous Lithium Ion Battery - Alias, Nurhaswani (2015)
An aqueous rechargeable lithium ion battery (ARLB) has become a great solution to overwhelm the cost and safety issue of the conventional lithium ion battery with organic electrolyte. Recently, the in situ carbon layer was proven to avoid any direct contact between the nanoparticles and the environment, including O2 and H2O. This help to achieve high capacity battery with improved capacity retention in aqueous environment. A citric acid assisted sol-gel method is employed in this study to prepare carbon-coated lithium iron phosphate (LiFePO4/C) using different calcination temperatures (500–800 °C). The phase structure and elemental analyses confirmed the orthorhombic crystal structure of LiFePO4 surrounded by different amounts of carbon layer. The morphologies and physical absorption results proved the porous structure of LiFePO4/C with a mesoporous range. The calcination temperature influences the crystallite size, impurity phase, and surface area as the LiFePO4/C calcined at 700 °C offered the optimum properties. This finding was supported by the electrochemical behavior of LiFePO4/C in the ARLB system with an air-electrode. The LiFePO4/C calcined at 700 °C showed the highest current response for cyclic voltammetry and the lowest impedance (6.11 Ω) with a good discharge capacity (83 mA h g−1 at 1.0 C). In addition, good cycling stability was achieved as the LiFePO4/C maintained a discharge capacity of approximately 90 mA h g−1 within 30 cycles at 0.5 C. By contrast, bare LiFePO4, which was calcined at the same calcination temperature (700 °C), exhibited poor electrochemical performance with high capacity fading (45 % within 30 cycles at 0.5 C) because of high 2 impedance (18.98 Ω). The rate capability of the LiFePO4/C calcined at 700 °C was also compared with that of a platinum counter electrode; the air-electrode still showed better cycling behavior.